ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫ ПЕДАГОГИКА ИЛИМИНИҢ ТИЙКАРҒЫ ДЕРЕКЛЕРИ СЫПАТЫНДА - Пазылов, Т.А. (FAN va JAMIYAT, 2021)
The article discusses the possibilities of using educational ideas inherited by us from the Karakalpak folklore.